The solubility of thorium in carbonate-bearing solutions at hydrothermal conditions. (1st August 2022) - Nisbet, Haylea; Migdisov, Artas A.; Williams-Jones, Anthony E.; van Hinsberg, Vincent J.; Xu, Hongwu; Roback, Robert
Abstract: Thorium mineralization is frequently hosted in carbonate-bearing rocks, and thorium commonly substitutes into the structures of carbonate-bearing minerals that have precipitated from or been modified by hydrothermal fluids. Given this common association, it is reasonable to consider the hypothesis that the presence of carbonate ligands in hydrothermal solutions promotes the transport of Th through the formation of stable aqueous complexes. Our ability to evaluate this hypothesis, however, is hindered by the lack of experimental data for Th-carbonate species at conditions beyond ambient. The low-temperature data indicate that carbonate is a strong complexing agent for Th. In this contribution, we investigate the solubility of Th in carbonate-bearing fluids relevant to natural systems (0.05–0.5 m NaHCO3 /Na2 CO3 ; pHT  ~ 7.8–9.8) at elevated temperature (175–250 °C). We demonstrate that, in contrast to the behavior of Th at low temperature, the stability of Th-carbonate complexes is not sufficient for them to predominate at these conditions. Instead, the solubility of Th is governed by hydrolysis reactions. Under the experimental conditions investigated, the predominant hydroxyl complexes are Th(OH)4 0 and Th(OH)5 − . Thermodynamic formation constants were derived for these species at the temperatures considered in our experiments (log β4  = 43.34 and 44.31 at 175 and 200 °C, respectively, and log β5  = 46.15 and 47.9 at 225 and 250 °C, respectively) to permit forward modeling of Th mobility in natural systems. Our study indicates that carbonate ions are unlikely to play a role in transporting Th in hydrothermal fluids. Summarizing the results of this study and our previous studies of the solubility of Th in hydrothermal fluids, we conclude that SO4 2− is the primary ligand responsible for the hydrothermal transport of Th.